Management of Valvular Disease During Pregnancy: Evolving Role of Percutaneous Treatment - Chiara Fraccaro; Noemie Tence; Giulia Masiero; Nicole Karam (Interventional Cardiology: Reviews, Research, Resources)
Valvular heart disease (VHD) is encountered in approximately 1% of pregnancies, significantly increasing both maternal and foetal risk. Rheumatic VHD remains the most common form in non-Western countries, whereas congenital heart disease dominates in the Western world. The risk of complications varies according to the type and severity of the underlying VHD. Moreover, pregnancy is a hypercoagulable state associated with increased risk of thromboembolism. The authors review the main VHDs encountered during pregnancy, and suggest management strategies based on the 2018 European Society of Cardiology recommendations for the management of pregnant women with VHD, providing an overview of classical and new transcatheter structural therapeutic options with a special focus on radiation exposure and anticoagulation drug management.